ANALYSIS OF PERCEIVED VALUE AND TRUST OF SATISFACTION AND ITS IMPACT ON THE LOYALTY OF ONLINE SHOPPING CONSUMERS IN TOKOPEDIA - Maesaroh, Fitria; Hari Aji, Wachyu (Dinasti Publisher, 2021)
The number of Internet Users is increasing and the competitors of Online Business are making Online Shopping business tight, but the increase in Internet users is not in line with the increase in Online Shopping users. Data obtained from the Association of Indonesian Internet Service Providers (APJII, 2020), the reason why Internet users never change their goods or services online 6.7% is worried that the goods will not arrive. And data from the National Consumer Protection Agency (BPKN) for 2018-2020 there were complaints with problems regarding phishing and accounts via OTP. Tokopedia is an E-marketplace Platform that carries Online Purchase of Goods, with Tokopedia, consumers can easily fulfill their daily needs. The development of Tokopedia is very convincing that many consumers are making products. The more consumers who make repeated purchases, the more growth will be. However, there will be repeated every consumer who feels loyal to what is offered and has a customer. Loyalty must have several components because Loyalty is built on the basis of several components. So that this research discusses the Perceived Value and Trust in Satisfaction and its impact on Consumer Loyalty. This study refers to previous research as a conceptual basis. The research sample was taken from 256 respondents who were taken from the Tokopedia application using Google Docs in the form of a questionnaire survey. From the results of this study, consumer loyalty is very hampered by the Perceived Value, trust and satisfaction as a mediation.